Linear groups : the accent on infinite dimensionality /: the accent on infinite dimensionality. (2020) - Dixon, Martyn R (Martyn Russell), 1955-; Kurdachenko, Leonid A, 1949-; Subbotin, Igor Ya, 1950-
No abstract available